An ANALISIS KEPUASAN KONSUMEN PADA AGROWISATA CILANGKAP KOTA JAKARTA TIMUR - Salsabila, Aprilia; Abubakar, Abubakar; Azzahra, Fatimah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Consumption has become a profitable business in order to extend the life of the agricultural industry. The best way to increase traffic is to increase the number of visitors. Consumption is one of the most important factors in the success of any business. The purpose of this study is to learn about the characteristics of people who visit, the frequency with which they visit, and the variety of people who visit. Peneliti selected 100 people as respondents using the purposive sampling method, with a likert scale used for scoring. The method of analysis used is quantitative deskriptif. Data analysis in this study employs Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the study show 1) The most common type of consumer is a woman, with a median age of 26 to 35 and a median level of education. In the upper school, around 72% have graduated and are working as housewife, The majority of consumers are women; the majority of them are between the ages of 26 and 35; their primary educational institution is Sekolah Menengah Atas; around 72% of them have already married; and, on average, they work as Ibu Rumah Tangga. 2) The attribute with the highest level of kepuasan in the country is the product being sold, and the attribute with the lowest level of kepuasan is the work itself. Customer Satisfaction Index Measurement of Consumer Satisfaction indicates that a score of at least 70,74% is considered to be satisfied.